2018
DOI: 10.3928/01913913-20180220-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Funduscopic Examination Using a Smartphone-Based Digital Ophthalmoscope and the Direct Ophthalmoscope

Abstract: The D-EYE digital ophthalmoscope is a practical device that could be incorporated into medical education and clinical practice. Survey results revealed that most students preferred the D-EYE digital ophthalmoscope due to the recording features and larger image of the fundus. [J Pediatr Ophthalmol Strabismus. 2018;55(3):201-206.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 3 publications
1
35
2
1
Order By: Relevance
“…[11][12][13][14] Direct ophthalmoscopy takes skill to perform and requires practice, however there is very little time spent learning ophthalmology in medical schools around the world. [11][12][13][14]16,17 Furthermore, time is a significant barrier for clinicians to practice and perform this skill in busy clinics. 11 Multiple alternatives for fundus examination have been developed including smart phone ophthalmoscopes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[11][12][13][14] Direct ophthalmoscopy takes skill to perform and requires practice, however there is very little time spent learning ophthalmology in medical schools around the world. [11][12][13][14]16,17 Furthermore, time is a significant barrier for clinicians to practice and perform this skill in busy clinics. 11 Multiple alternatives for fundus examination have been developed including smart phone ophthalmoscopes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Multiple alternatives for fundus examination have been developed including smart phone ophthalmoscopes. 15,17,18 These consist of a lens adapter attached to a smart phone camera. 14,17,18 Many studies have suggested that smart phone ophthalmoscopy may be easier to teach in medical school and is preferred by medical students.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works are interested to the quality of fundus image captured by Smartphone, with respect to the clinical employment. The work described in [32] describes an experimentation that evaluates the D-EYE lens captured fundus images with respect to the direct ophthalmoscope ones. A rating between 0 and 5 is asked from 25 patients to each picture.…”
Section: Quality Of Smartphone-captured Fundus Imagesmentioning
confidence: 99%